CHARACTERISATION OF SOYBEAN RHIZOBIAL STRAINS FROM JAVA AND SUMATRA - Waluyo, Setiyo Hadi; Lie, Tek An; Mannetje, Leendert’t; de Vos, Willem M. (Indonesian Agency for Agricultural Research and Development - MOA, 2005)
To get insight in the structure of soybean rhizobial populationnative to Indonesian soils, a thorough survey of the occurrenceof the soybean rhizobia were conducted in several locations inJava and Sumatra. A total of 51 different isolates of rhizobialstrains were characterised phenotypically based on their symbioticproperties, and genetically using amplified ribosomal DNArestriction analysis (ARDRA). Based on their nodulation capacityon both soybean and the native legume mungbean, these rhizobialstrains could be divided into a group of 16 strains specific forsoybean only and another group of 35 promiscuous strains thatnodulated both leguminous plants. Based on ARDRA of PCRamplified16S rDNA and 16S-23S rDNA spacer fragments, therhizobial strains isolated from Java differed with those fromSumatra. Six Java isolates and only one Sumatra isolate wereclassified as Bradyrhizobium japonicum and these similar to thatof B. japonicum strain USDA 110. All these B. japonicum strainswere highly specific for soybean. One isolate from Java showeda rather unique position. The remaining strains from Java (20),which were symbiotically promiscuous strains, were clustered inanother group. This group and another group containing mostSumatra isolates were distinct from B. japonicum USDA 110 andtherefore it is tempting to speculate that these represent indigenoussoybean rhizobial bacteria. Application of agriculturalpractices, such as enhancement of rhizobial population, toincrease soybean production is still essential and noteworthy inSumatra.